Determination of the glycemic index values of the Turkey-specific ice cream - Yumuk, Nuket; Keskin, Çağlar; Demir, Özgür; Şahin, Mustafa; Bahçecioğlu Mutlu, Adile Begüm; Canlar, Şule; Emral, Rıfat; Erdoğan, Murat Faik; Güllü, Sevim; Tonyukuk Gedik, Vedia; Başkal, Nilgün; Çorapçıoğlu, Demet (Acta Medica, 2022)
Objective: The glycemic index (GI) is defined as the effect of consumed food on blood glucose relative to the reference food. The aim of this study is to determine the GI value of “Atatürk Orman Çiftliği (AOÇ)” ice cream, which is unique to our country. Method: This study included 18 adult healthy individuals with normal body mass index (BMI) values (18.5-24.9 kg/m²) (Female/Male: 10/8). Individuals participating in the study were invited to the our outpatient clinic on different days for two weeks to consume 2 test foods (AOC ice cream) and 2 reference foods (glucose) after 12 hours of fasting. Venous blood samples were taken at 0, 15, 30, 45, 60, 90 and 120 minutes after consumption of reference and test foods and glucose values were recorded. The glycemic index value of the test food was calculated by multiplying by 100 the ratio of the sum of the area under the curve obtained from the test food to the sum of the area under the curve obtained from the reference food. Results: The median values of the area under the curve of the reference food and the test food were 2360.88 (483.75-4132.5) and 475.95 (44.88-1980), respectively (p<0.001). The Glycemic index value of the test foods was 21.46 (4.08-409.3) according to the reference food. Conclusion: In this study, the glycemic index value of the Turkey-specific “Atatürk Orman Çiftliği” ice cream was found to be 21,46 (4.08-409.3) (Low). These types of foods with a low glycemic index may be preferred to increase the dietary compatibility of the patient with type 2 diabetes, especially at snack meals.